Pemanfaatan Elektrolit Air Laut Sebagai Sumber Energi Listrik Baterai Dengan Elektroda Tembaga - Aluminium - Zuffa Anisa; Dyah Setyaningrum (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
Electrical energy demand is increasing from time to time. Most sources of electrical energy come from petroleum, natural gas, and coal. Even though this energy source is non-renewable, the amount is dwindling, and it produces carbon emissions that can cause the greenhouse effect. Indonesia is an agrarian country whose territory is more than seventy percent of the ocean. Natural resources: seawater and beach sand are certainly very abundant. In this study, this natural material is used by researchers as a source of electrical energy in the form of a battery. As far as researchers know, research on the manufacture of battery cells by direct use of natural resources does not yet exist. Much is preliminary research on the extraction of basic materials so almost all research on batteries costs a lot of money by methods that are not simple. Therefore, this research is very important, because it uses a simple assembly method which is certainly time-saving and cost-effective. The battery array made consists of [Cathode || Electrolyte + Microporous Separator || anode]. The seawater-salt water battery cells made successfully turn on the lights, both LED lamps, and home light bulbs, with a large current generated of 13.56mA. The voltage produced by a battery cell is 1.31 V, while the series voltage for 2-3 batteries is 2.55 V and 3.6 V, respectively.